2021
DOI: 10.3390/rs13040805
|View full text |Cite
|
Sign up to set email alerts
|

Intraday Variation Mapping of Population Age Structure via Urban-Functional-Region-Based Scaling

Abstract: The spatial distribution of the population is uneven for various reasons, such as urban-rural differences and geographical conditions differences. As the basic element of the natural structure of the population, the age structure composition of populations also varies considerably across the world. Obtaining accurate and spatiotemporal population age structure maps is crucial for calculating population size at risk, analyzing populations mobility patterns, or calculating health and development indicators. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…If the model RMSE is significantly reduced due to the introduction of feature variables, such features are retained for their eventual participation in the modeling; otherwise, such variables are removed. RF-RFE quantifies the modeling relevance of each feature based on its classification contribution [63][64][65].…”
Section: Feature Preference and Importance Rankingmentioning
confidence: 99%
“…If the model RMSE is significantly reduced due to the introduction of feature variables, such features are retained for their eventual participation in the modeling; otherwise, such variables are removed. RF-RFE quantifies the modeling relevance of each feature based on its classification contribution [63][64][65].…”
Section: Feature Preference and Importance Rankingmentioning
confidence: 99%
“…OSM road network data are part of a popular Volunteer Geographic Information project (VGI) [39] and are characterized by high positioning accuracy, regular updates, and free access. The OSM is an internal segmentation of urban land use [40] and is suitable for the study of urban functional areas [41].…”
Section: Plot Datamentioning
confidence: 99%
“…OSM road network data are part of a popular Volunteer Geographic Information project (VGI) [39] and are characterized by high positioning accuracy, regular updates,…”
Section: Plot Datamentioning
confidence: 99%
“…One of the most commonly used methods, employed in previous feature optimisation studies, is recursive feature elimination based on SVM (SVM-RFE) [32,33]. Meanwhile, an increasing number of studies have combined random forest algorithms with RFE for feature optimisation [34][35][36]. Meanwhile, related studies have reported that RF-RFE is a mature feature selection method that offers superior results to SVM-RFE [37].…”
Section: Uav Remote Sensing Feature Selectionmentioning
confidence: 99%